Avaliação da expressão gênica de micrornas e do perfil inflamatório de pacientes transplantados renais em um estudo longitudinal prospectivo. - Lorraine Vieira Alves (2024)
Long-term monitoring of kidney transplant patients is crucial for assessing transplant stability and promoting necessary clinical interventions for graft survival. There is a need to complement this monitoring with promising biomarkers to enable earlier detection of graft dysfunction and optimize post-transplant treatment adjustments. The aim of this study was to evaluate an inflammatory and genetic panel in renal transplant recipients (RTR) and relate it to graft function and patients' clinical outcomes. Sixty-nine RTR were grouped based on renal function using 2016 creatinine levels for estimated glomerular filtration rate (eGFR) calculation, with R1 being eGFR < 60 and R2 being eGFR ≥ 60 mL/min/1.73m². They were also categorized based on stable renal function (SRF) and primary outcome (PO), defined as a greater than 30% decrease in eGFR and/or return to dialysis and/or rejection and/or retransplantation. Cytokines, chemokines, and homocysteine (HC) were measured by ELISA, MILLIPLEX® Multiplex Assay, and Colorimetric Enzyme Assay. MicroRNA (miRNA) expression was determined by RT-qPCR. Medical records data were collected from 2016 to 2021. Higher levels of CXCL10 were found in the R1 group compared to the R2 group (p = 0.037). Additionally, patients who reached the PO had elevated levels of CXCL10 (p = 0.024) and HC (p = 0.033) compared to those who maintained stable renal function throughout the follow-up. CXCL10 showed good performance in discriminating between PO and SRF (p = 0.024). Some inflammatory biomarkers correlated with each other, and CXCL10 correlated with creatinine levels. In the evaluation of immunosuppressive therapy, patients not using either of the two main immunosuppressants, Tacrolimus (TAC) and Cyclosporine A (CsA), had higher levels of IL-6 than those using TAC (p = 0.028) or CsA (p = 0.009), but there was no significant difference in the inflammatory panel between TAC or CsA users. Regarding miR-145-5p, higher gene expression (2.05x) was found in the R2 group, patients with better renal filtration function, compared to the R1 group (p = 0.014). As for miR-23b-3p, higher gene expression (1.36x) was observed in the R1 group compared to the R2 group (p = 0.001). Regarding miR-15a-5p, higher gene expression was found in R1 group patients (8.44x) and in patients who reached the PO (5.96x) compared to those with better eGFR (p = 0.010) and those who maintained SRF throughout the clinical follow-up until 2021 (p < 0.001). Concerning miR-15b-5p, higher gene expression (5.91x) was found in the SRF group compared to the PO group (p = 0.002). Additionally, higher gene expression (2.11x) of miR-15b-5p was observed in the group with better renal function (R2) compared to the R1 group (p = 0.003). The choice between TAC or CsA did not significantly impact the inflammatory profile of RTR. Incorporating CXCL10 and the proposed miRNA panel into clinical practice could enhance therapeutic interventions to potentially improve renal allograft survival.